Studi Implementasi dan Analisis SWOT Kepatuhan Syariah di Multazam Hotel Solo - Faruk, Ahmad; Sukoco, Bambang; Qoway, Octiana Atika (Jurnal Ilmiah Ekonomi Islam, 2024)
The implementation of sharia compliance results in obstacles that must be faced by management in the sharia hotel business. So far, sharia hotel management strategies in facing obstacles to the implementation of sharia compliance have not been studied much, the majority of studies that have been conducted have been to examine business strategies with the aim of profitability. The urgency of this research is to fill the gap in the literature on implementation case studies and SWOT analysis of sharia compliance in the hotel business. Implementing sharia compliance is the essence of sharia hotel operations, which is a differentiating factor from conventional hotels and is more important than profitability goals. The aim of this research is to determine the implementation of sharia compliance and the SWOT strategy for sharia compliance by conducting a case study analysis at the Multazam Syariah Hotel. Data analysis on the implementation of sharia compliance was carried out using an exploratory qualitative approach, while the sharia compliance strategy was carried out using SWOT analysis. The research results show that Multazam Syariah Hotel has implemented sharia compliance in the Human Resources (HR), Facilities and Business aspects, but there are several parts that need to be strengthened. SWOT analysis shows points of strength (such as: Sharia Brand Image and halal certification for food and beverage product management); weaknesses (such as: Not yet having a sharia supervisor and compatibility of facilities with sharia); opportunities (such as: The hotel environment is around Islamic educational institutions and the majority of guests are Muslim); as well as challenges (such as: Illegal couple guests and lack of public knowledge about sharia hotels).